Trauma exposure and ICD-11 PTSD and CPTSD in a Greenlandic adolescent population - Trine Banzon; Maria Louison Vang; Sille Schandorph Løkkegaard; Ask Elklit (European Journal of Psychotraumatology)
Background: Little peer-reviewed research has been done on trauma exposure, Post-Traumatic Stress Disorder (PTSD) and Complex PTSD (CPTSD) prevalence among Greenlandic children and adolescents. There is a need for a validated Greenlandic version of the International Trauma Questionnaire – Child and Adolescent version (ITQ-CA) to assess symptoms of ICD-11 PTSD and CPTSD, as well as investigations of the prevalence of these disorders. This information is imperative in a Greenlandic context, where general epidemiological knowledge on traumatic exposure and reactions is lacking.Objective: The present study examined the factor structure of the Greenlandic ITQ-CA, estimated the prevalence of trauma exposure, ICD-11 PTSD and CPTSD, and examined the relationship between potentially traumatic events (PTEs), PTSD, CPTSD, and demographic variables in a Greenlandic adolescent population.Method: Confirmatory factor analysis of competing models of the dimensionality of the ITQ-CA was tested among Greenlandic adolescents (N = 704) aged 11–17 years (M = 13.4, SD = 1.77). Using the ITQ-CA, PTSD and CPTSD was assessed.Results: Findings supported the factorial validity of the Greenlandic ITQ-CA although factor structure differed across boys and girls. A total of 82.8% of the adolescents had been directly exposed to at least 1 PTE (M = 3.2), and 57.0% had been indirectly exposed (M = 3.1). The estimated prevalence of PTSD and CPTSD was 7.8% and 8.5%, while an additional 13.9% and 7% reached subclinical levels. Older age, female gender, several different and cumulative PTEs significantly elevated the risk of PTSD and CPTSD.Conclusion: ITQ-CA is a valid tool for identifying symptoms of ICD-11 PTSD and CPTSD. Results indicate that type and quantity of direct traumatic exposure are important predictors of PTSD and CPTSD. Events not normally considered traumatic as well as non-interpersonal events are significantly associated with CPTSD symptoms.